Optimization of aqueous extraction of phenolic compounds and bioactive profiles from brown (Sargassum polycystum) and red (Kappaphycus alvarezii) seaweeds using the response surface method - Eko Murdiono, Wisnu; Ab Razak, Nor Asma; Yong, Jean; Effendi Halmi, M. Izuan; Mahmud, Khairil (Elsevier, 2025)
Seaweed is becoming increasingly attractive in research because of its fast growth, highly adaptive to a broad range of environmental conditions, and rich in bioactive compounds. It can potentially be harnessed as a bio fertilizer for growing plants. Water is an effective and “green” solvent to extract phenolic compounds. However, the aqueous extraction of seaweed containing polyphenols and their bioactivity has been less reported. Therefore, the present work aimed to examine the aqueous extracts of phenolic substances in Malaysian red and brown seaweed by applying the response surface methodology (RSM). Interestingly, the optimum extraction conditions among red and brown seaweed were different. The optimised extraction conditions for red seaweed were 40◦ and 40 mL g 1◦ C, 30 min solvent ratio generating 30.05 % yield, 0.075 mg GAE/g total phenol, 0.0175 mg QE/g total flavonoid and 10.04 % inhibition of DPPH assay. Meanwhile, the optimum extraction conditions for brown seaweed are 80 °C, 83 min and 40 mL/g 1 solvent ratio, producing 22.90 % yield, 0.217 mg GAE/g phenolic content, 0.034 mg QE/g flavonoid content and 6.25 % inhibition of DPPH assay. We successfully identified five compounds, three of which were present in both seaweeds, while two compounds were unique to the brown seaweed. These compounds can potentially be used as antimicrobials, growth stimulants, and immunostimulants. Moving forward, the aqueous extracts derived from the two seaweeds contain suitable and valuable bioactive compounds for developing novel biostimulant-based biofertilizer.